Introduction to Special Issue: The Mutual Influence of Religion and Science in the Human Understanding and Exploration of Outer Space - Weibel, Deana L. (Religions, 2021)
When considering the exploration of outer space people typically think about technology, engineering, physics, and the use of the scientific method to understand what is out there, beyond the Earth’s atmosphere, from the nearby Moon to distant galaxies only visible through the use of high-powered telescopes [...]